Sustitución de las penas privativas de libertad, para las personas que en las provincias fronterizas, puertos marítimos, o mar territorial, transporten o comercialicen sin la debida autorización productos derivados de hidrocarburos - Vargas Torres, Maritza Nelly (2015)
The current thesis entitled "Replacing imprisonment for people in the border provinces, ports or territorial sea, transported or marketed without authorization hydrocarbon derivatives", my interest is projected to develop it, the observed daily legal to low-income people are subjected to market products or transporting oil or liquefied petroleum gas, with this kind of people that justice punishes them severely problems, while large smugglers to evade operating the governments because they are alerted to these repressive events. The problem of smuggling across borders and seaports is a never ending problem, because every day these activities has become a business that allows them to survive economically disadvantaged persons engaged in this activity are made unlawful. Although there are criminal and operational policy by the Ministry of Interior has not been possible to curb smuggling since the seventies has been developing in each government. People processed by small amounts of fuel are deprived of their liberty, without allowing another alternative to imprisonment, so far the State violates the constitutional rule that imprisonment is a last resort and should be issued other which do not restrict individual freedom of individuals. With the force of the Code Integral Penal the offense of crimes transportation, marketing or illegal distribution of hydrocarbons is typified, including liquefied petroleum gas or biofuels, in the border provinces, maritime or inland or territorial sea ports, I punished with imprisonment for five to seven years. This sentence should be modified and allowed the imprisonment of Art. 60 of the Code prior to ensure personal integrity and right to individual liberty of the accused, with community work. The development of literature and the results of the survey and interviews allowed me to get criteria, with clear and precise basis of well known literature, which contributed to the verification of targets, and the testing of the hypothesis, allowing support changes Integral proposed the Organic Code of Criminal Procedure. The content of this thesis is the result of an arduous legal research of the author in the scientific, legal, social and methodological level, addressing theories and knowledge obtained through techniques